2011
DOI: 10.1186/1476-511x-10-197
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of the hepatic lipase gene polymorphism c.514C > T with estrogen replacement therapy response

Abstract: BackgroundHepatic lipase (HL), an enzyme present in the hepatic sinusoids, is responsible for the lipolysis of lipoproteins. Human HL contains four polymorphic sites: G-250A, T-710C, A-763G, and C-514T single-nucleotide polymorphism (SNPs). The last polymorphism is the focus of the current study. The genotypes associated with the C-514T polymorphism are CC (normal homozygous - W), CT (heterozygous - H), and TT (minor-allele homozygous - M). HL activity is significantly impaired in individuals of the TT and CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Whitcroft et al [4] reported that transdermal estradiol treatment for post-menopausal women could lower serum TG levels by about 16.4% ( P  < 0.01). Pulchinelli et al [5] found that estrogen replacement therapy statistically reduced TG levels of hysterectomized women. A meta-analyzed further confirmed a modest effect of transdermal estradiol treatment on decrease of serum TG levels [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whitcroft et al [4] reported that transdermal estradiol treatment for post-menopausal women could lower serum TG levels by about 16.4% ( P  < 0.01). Pulchinelli et al [5] found that estrogen replacement therapy statistically reduced TG levels of hysterectomized women. A meta-analyzed further confirmed a modest effect of transdermal estradiol treatment on decrease of serum TG levels [6].…”
Section: Introductionmentioning
confidence: 99%
“…14,15,17,20,21,[37][38][39] However, the G-250 and C-514 alleles are relatively less frequent in Japanese, Iranians, Chinese, Koreans, Americans, and Brazilians. 7,8,12,13,18,19,[22][23][24][25]40,41 In this study, only two polymorphisms in LIPC gene were examined. However, other LIPC gene variants, such as C-480T, are associated with lipid profile and CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Both C-514T and G-250A SNPs are associated with cardiovascular diseases (CVDs). [14][15][16][17][18] The distribution and clinical significance of LIPC C-514T and G-250A polymorphisms have been extensively investigated among the Europeans, Asians, and Americans, 12,13,15,17,[19][20][21][22][23][24][25] while they are still widely unknown among Arabs. Therefore, in this study, LIPC C-514T and G-250A polymorphisms and association with plasma lipid profile in young Jordanians were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms that estrogen and lipid interact at a molecular level to contribute to the risk of CVD are not clear. It has been reported that estrogenrelated receptor γ (ERRγ) regulates hepatic TG metabolism through the action phospholipase A2G12B [44], and polymorphic hepatic lipase is associated with estrogen modulate lipolysis of TG [45]. Della Torre et al showed that liver ERα activity was essential for balanced lipid and TC metabolism, lack of ERα might lead to hepatic fat accumulation and nonalcoholic fatty liver disease [46].…”
Section: Lipid Metabolism At Menopausementioning
confidence: 99%
“…Numerous studies have attempted to understand the metabolic consequences of MHT use and define the effects of different MHT regimens. Major studies have consistently found MHT decrease LDL-C, TC and lipoprotein (a) levels; however, findings regarding TG and HDL-C levels have been inconsistent [45,[54][55][56][57]. Godsland reviewed the effect of different MHT regimens, estrogen alone, estrogen plus progestogen, raloxifene, or tibolone on plasma lipid and lipoprotein levels and found estrogen alone raise HDL-C and lower LDL-C and TC.…”
Section: Menopausal Hormone Therapy-related Lipid Metabolismmentioning
confidence: 99%